‘None but Ourselves Can Free Our Minds’: Review of "A Community Life: Memoirs of Alfred M. Sears" - Dean, Ann Victoria (International Journal of Bahamian Studies, 2017)
Review of A Community Life: Memoirs of Alfred M. Sears: A Redemption Story from Reform School to Attorney General and Minister of Education of the Bahamas, Alfred M. Sears. I-EASE Publishack, 2017. ISBN 978-978-8201-14-4 This emotionally charged testimonial to life in the historical colonial and postcolonial Bahamas is a deeply politicized story of personal and political redemption built on Alfred Sears’ decades-long commitment to literacy and education, to the value of family and community and to the practice of speaking truth to power. Sears argues that both the health of Bahamian society and the sovereignty of the nation are dependent on its citizens being able to think for themselves and for that to happen, it is imperative to root out the legacies of colonialism. He makes recommendations for altering the Bahamian Constitution and thematically addresses concerns about government corruption, transparency, and accountability; partisan polarization; the Bahamian politic as a system of patronage and clientelism; the need for constitutional reform; political campaign finance reform; sustained economic development and participatory regionalism.